The wisdom of Buddhism (Michael Joseph, 1960)
A balanced selection from Buddhist writings, including scriptures used by the Zen School, with chapters on the Buddha, Tibetan Buddhism, Concentration and Meditation, the Buddhist Order, and Nirvana. With sources, glossary and index.